Comrade or Brother? : a history of the British labour movement - Davis, Mary, 1947- (Pluto Press, 2009)
'The book stands comparison with A.L. Morton's 'People's History' and G.D.H. Cole's 'Common People'. But it is more than just this. It is in a real sense a history for our own times.' John Foster, Emeritus Professor, University of the West of Scotland'This book is ideal for its purpose. I only wish it had been available in the decades when I was teaching trade union courses.' Jim Fryth, Labour History Review'At last a readable and accessible general history of the labour movement ... Highly recommended.' Manchester TUC Newsletter--A revised, updated and expanded edition of this classic feminist account of British labour history--Critical and iconoclastic, Comrade or Brother? traces the history of the British Labour Movement from its beginnings at the onset of industrialisation through its development within a capitalist society, up to the end of the twentieth-century. Written by a leading activist in the labour movement, the book redresses the balance in much labour history writing. It examines the place of women and the influence of racism and sexism as well as providing a critical analysis of the rival ideologies which played a role in the uneven development of the labour movement.